ANALISIS PERSEPSI MASYARAKAT TERHADAP DAMPAK DEPOSISI ABU VULKANIK GUNUNG MARAPI DAN STRATEGI PRODUKTIVITAS PERTANIAN DI KAWASAN KOTA PADANG PANJANG - Putra Kumbara; Nefilinda; Trina Febriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The 2023–2024 eruption of Mount Marapi resulted in volcanic ash deposition that significantly affected the agricultural sector in Padang Panjang City. This study aims to analyze community perceptions of the impact of volcanic ash on agricultural productivity, identify farmers’ adaptation strategies, and examine the role of government and related institutions in supporting agricultural recovery. The research employed a mixed-methods approach with descriptive quantitative and qualitative designs. Data were collected through questionnaires distributed to 100 affected farmers, key informant interviews, field observations, and documentation. Quantitative analysis used frequency distribution, Likert scale scoring, and the Respondent Achievement Level (TCR). The results indicate that the impact of volcanic ash falls into a high category (TCR 81%), characterized by ash-covered farmland, difficulties in soil cultivation, crop damage, increased crop failure, and decreased yields and farmer income. Farmers’ adaptation strategies include land rehabilitation, changes in cropping patterns, the use of organic fertilizers, and strengthened farmer group cooperation, which are considered fairly effective in reducing losses. The government contributed through the provision of agricultural inputs, extension services, and infrastructure improvement, although the distribution of assistance remains limited. This study highlights the importance of local-based adaptation strategies and institutional support to sustain agricultural productivity in volcanic hazard-prone areas.